Comprehensive analysis of endoplasmic reticulum stress-associated genes signature of ulcerative colitis - Deng, Beiying; Liao, Fei; Liu, Yinghui; He, Pengzhan; Wei, Shuchun; Liu, Chuan; Dong, Weiguo (Frontiers in Immunology, 2023)
Background Endoplasmic reticulum stress (ERS) is a critical factor in the development of ulcerative colitis (UC); however, the underlying molecular mechanisms remain unclear. This study aims to identify pivotal molecular mechanisms related to ERS in UC pathogenesis and provide novel therapeutic targets for UC. Methods Colon tissue gene expression profiles and clinical information of UC patients and healthy controls were obtained from the Gene Expression Omnibus (GEO) database, and the ERS-related gene set was downloaded from GeneCards for analysis. Weighted gene co-expression network analysis (WGCNA) and differential expression analysis were utilized to identify pivotal modules and genes associated with UC. A consensus clustering algorithm was used to classify UC patients. The CIBERSORT algorithm was employed to evaluate the immune cell infiltration. Gene Set Variation Analysis (GSVA), Gene Ontology (GO), and Kyoto Encyclopedia of Genes and Genomes (KEGG) were used to explore potential biological mechanisms. The external sets were used to validate and identify the relationship of ERS-related genes with biologics. Small molecule compounds were predicted using the Connectivity Map (CMap) database. Molecular docking was performed to simulate the binding conformation of small molecule compounds and key targets. Results The study identified 915 differentially expressed genes (DEGs) and 11 ERS-related genes (ERSRGs) from the colonic mucosa of UC patients and healthy controls, and these genes had good diagnostic value and were highly correlated. Five potential small-molecule drugs sharing tubulin inhibitors were identified, including albendazole, fenbendazole, flubendazole, griseofulvin, and noscapine, among which noscapine exhibited the highest correlation with a high binding affinity to the targets. Active UC and 10 ERSRGs were associated with a large number of immune cells, and ERS was also associated with colon mucosal invasion of active UC. Significant differences in gene expression patterns and immune cell infiltration abundance were observed among ERS-related subtypes. Conclusion The results suggest that ERS plays a vital role in UC pathogenesis, and noscapine may be a promising therapeutic agent for UC by affecting ERS.